Particularities of the Implement of Quality Management System Based on the Requirements of the ISO 9001 in the Telecommunications Companies - Verkhovskaya, Marina V.; Men'shikova, Ekaterina V.; Khazanov, Oleg V. (International Review of Management and Marketing, 2016)
This article describes the advantages of the implementing of quality management system based on the ISO 9001 in the telecommunications companies. The stages of the implementation of the quality management system in the telecommunications companies are discussed. The card of main process and criteria of processes are developed. The expediency of implementing the quality management system based on the requirements of ISO 9001 in Telecommunications is showed. Keywords: system, quality, management, process, introduction. JEL Classifications: D23, L23